A Highly Efficient Magnetic Iron(III) Nanocatalyst for Ferrier Rearrangements - Dong, Youxian; Ding, Zekun; Guo, Hong; Zhou, Le; Jiang, Nan; Chen, Heshan; Qiu, Saifeng; Xu, Xiaoxia; Zhang, Jianbo (Synlett, 2019)
A novel and highly efficient magnetic Fe3O4@C@Fe(III) core–shell catalyst, in which the carbon shell was prepared from lotus leaf, was fabricated. This nanocatalyst was successfully applied in the synthesis of a series of 2,3-unsaturated O-glycosides in excellent yields and with high selectivity, especially in the case of 2-halo O-glycosides, which differ in reactivity from nonsubstituted O-glycosides, but which have scarcely been explored before. Moreover, the catalyst could be easily separated from the reaction by the application of an external magnetic force and reused a minimum of five times without any significant decrease in the yields of the products. In addition, the reaction proceeded readily on a gram scale, which provides a bright prospect for future applications.
Keywords: nanocatalyst; Ferrier rearrangement; haloglucals; iron catalysis; catalyst recycling; magnetic catalyst